2017
DOI: 10.1002/hep.28992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intensive lifestyle intervention program on portal hypertension in patients with cirrhosis and obesity: The SportDiet study

Abstract: Obesity increases the risk of clinical decompensation in cirrhosis, possibly by increasing portal pressure. Whether weight reduction can be safely achieved through lifestyle changes (diet and exercise) in overweight/obese patients with cirrhosis, and if weight loss reducesportal pressure in this setting is unknown. This prospective, multicentric, uncontrolled pilot study enrolled patients with compensated cirrhosis, portal hypertension (hepatic venous pressure gradient, HVPG≥ 6mmHg) and body mass index (BMI)≥2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
189
0
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(234 citation statements)
references
References 27 publications
(58 reference statements)
7
189
0
9
Order By: Relevance
“…Prior studies, consisting of 6‐60 participants, have mainly focused on face‐to‐face, supervised exercise interventions in the hospital setting and in patients without significant liver failure warranting LT . In agreement with our findings, the safety, acceptability, and adherence of variable exercise programs in patients with MELD scores of 9‐13 was considered satisfactory .…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies, consisting of 6‐60 participants, have mainly focused on face‐to‐face, supervised exercise interventions in the hospital setting and in patients without significant liver failure warranting LT . In agreement with our findings, the safety, acceptability, and adherence of variable exercise programs in patients with MELD scores of 9‐13 was considered satisfactory .…”
Section: Discussionsupporting
confidence: 88%
“…A small pilot study demonstrated that adapted physical activity may improve the index of fitness and the quality of life in cirrhotic patients listed for LT [132]. Additionally, weight loss may reduce portal hypertension as well [133]. However, if lifestyle changes alone can reverse severe cirrhotic NASH is still unproven.…”
Section: How To Optimize the Outcome Of Nafld Patients Undergoing Ltmentioning
confidence: 99%
“…Insulin resistance, total cholesterol, and leptin levels improved as well. Because exercise was not intense and frequent enough to improve muscle mass, the demonstrated changes were likely related to weight loss …”
Section: Interventions Targeting Sarcopenia and Physical Fitnessmentioning
confidence: 99%